Antifeedant Effects of Essential Oil, Extracts, and Isolated Sesquiterpenes from Pilgerodendron Uviferum (D. Don) Florin Heartwood on Red Clover Borer Hylastinus Obscurus (Coleoptera: Curculionidae) - Urzua-Moll, A; Echeverria-Morgado, J; Gonzalez-Teuber, M (Multidisciplinary Digital Publishing Institute (MDPI), 2018)
The beetle Hylastinus obscurus Marsham (Coleoptera: Curculionidae), endemic to Europe and Northern Africa, is one of the most important red clover pests in Chile. As commercial insecticides are less effective against this pest, plant secondary metabolites have been considered as an alternative for its control. Here, we have investigated the chemical composition of essential oil (EO), petroleum ether extract (PEE), and dichloromethane extract (DCME) from Pilgerodendron uviferum heartwood. Additionally, the effects of EO and extracts on the feeding behavior (% of weight shift) of H. obscurus have been evaluated. The composition of EO, PEE, and DCME were analyzed using gas chromatography (GC) and gas chromatography/mass spectrometry (GC/MS). The results showed the presence of a similar mixture of sesquiterpenes in the essential oil and in both of the extracts, which accounted for circa 60% of the total mixture. Sesquiterpenes were further isolated using chromatographic methods and were structurally characterized by optical rotation, GC–MS, FTIR, and 1D and 2D NMR experiments. The physicochemical properties of the isolated sesquiterpenes, including lipophilicity and vapor pressure, were also determined. The sesquiterpenes were identified as the following: (−)-trans-calamenene (1), cadalene (2), (−)-cubenol (3), (−)-epi-cubenol (4), (−)-torreyol (5), and (−)-15-copaenol (6). The antifeedant activity of EO, extracts, and isolated sesquiterpenes were evaluated using artificial diets in a non-choice test. Relative to the control, the EO, DCME extract, and the isolated sesquiterpenes, namely, (−)-trans-calamenene (1), cadalene (2), and (5) torreyol, were found to be the most effective treatments against H. obscurus. Our study showed that the compounds occurring in P. uviferum heartwood were effective in reducing the adult growth of H. obscurus. The physicochemical properties of the isolated sesquiterpenes might have been associated with antifeedant effects. © 2018 by the authors.